A Study on the influence of workers on intellectual productivity when working with clothes with attachment / Sawada Hirotaka ... [et al.] - Hirotaka, Sawada; Yuji, Matumoto; Li, Andrew I-kawg; Ryusuke, Naka (2018)
Increasing global competition due to globalization, diversification of people's values and so forth, has further increasedthe need for improvement in intellectual productivity in offices.However, various factors affect the improvement of intellectual productivity. However, a method to directly measure intellectual productivity has not been established yet.Therefore, empirical studies that quantitatively capture intellectual productivity by using proxy variables of intellectual productivity have been accumulated so far.In addition, we sometimes make a special meaning to a particular thing, as we say "attaching" to things.Watanabe(2016) pointed out that "attachment" held by people on things play a role in improving psychological value such as amplifying the sense of happiness caused by ownership and realizing identity .In this study, therefore, the researcherhypothesized that intelligent productivity will improve if you do work with attached clothes. So the subject of an experiment to evaluate “work efficiency” as a subjective evaluation and “VAS evaluation of intellectual activity degree” which are a proxy variable of intellectual productivity was carried out. As a result, it cannot be said that the work efficiency is affected by wearing attached clothes, but when a group who replied that they feel attachment less than 50% of their own clothes wear attached clothes, it was found that the results improved which was established by influencing the convergent thinking work which leads one correct answer based on already existing information. In addition, it was discovered that in this group, compared with the time of wearing clothes without attachment, immediately before the work, their global vigor, global affect, happiness, and calmness is higher and immediately after the work their global affect is high and sadness is low.